2012
DOI: 10.5115/acb.2012.45.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Variant insertion of the teres major muscle

Abstract: The teres major (TerMa) muscle has a clinical significance for tendon transfer procedures in patients with massive rotator cuff tears. Individually, it originates from the dorsum of the inferior angle of scapula and inserts into the medial lip of bicepital groove of the humerus. Functionally, TerMa in cooperation with latissimus dorsi (LD) adducts arm, medially rotates arm, and assists in arm extension. The variation of TerMa insertion is very rare. In the shoulder and axillary regions of a 33-year-old Thai ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 6 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…40 Running deep and superior to the latissimus dorsi, the teres major originates from the posterior aspect of the inferior corner of the scapula and inserts just medial to the intertubercular groove and the latissimus dorsi insertion. 22 Surgical and cadaveric dissections have demonstrated that the latissimus dorsi and teres major tendons are often adherent to each other or that the teres major tendon may insert into the latissimus dorsi tendon. 4,32,39 Morelli et al 36 showed that in 15 of 18 shoulder specimens, the 2 tendons were confluent before separate humeral insertions.…”
Section: Anatomymentioning
confidence: 99%
“…40 Running deep and superior to the latissimus dorsi, the teres major originates from the posterior aspect of the inferior corner of the scapula and inserts just medial to the intertubercular groove and the latissimus dorsi insertion. 22 Surgical and cadaveric dissections have demonstrated that the latissimus dorsi and teres major tendons are often adherent to each other or that the teres major tendon may insert into the latissimus dorsi tendon. 4,32,39 Morelli et al 36 showed that in 15 of 18 shoulder specimens, the 2 tendons were confluent before separate humeral insertions.…”
Section: Anatomymentioning
confidence: 99%